Creating Public Innovation Through Public Values (Public Value) Case Study In Education Department City Of Surabaya - Supriyanto Supriyanto (Indonesian Association for Public Administration (IAPA), 2018)
This article will examine in depth the concept of public sector innovation, the process of creating public sector innovation and whether it is based on the public value. As a study material the author specializes in innovations created by the Surabaya City Education Office because there are seventeen innovations produced. Most innovations in the public sector are created as a reaction to a crisis when new leaders want to show that they are capable. Consequently the public sector innovation is not able to increase organizational capacity so that innovation tends to be unsustainable. Innovation will stop when the initiator is gone, so visionary leadership and innovation are needed to have compatibility with the system outside of itself and in harmony with relevant regulations and institutions. Innovation will remain sustainable without being influenced by the change of public leadership if it is sourced from public value because public innovations that are created from public values will remain strong to defend and the tendency is increased due to community support.